Description of a New Subgenus, Three New Species, and Taxonomic Problems of the Genus Allolobophora sensu Mrsic and Sapkarev, 1988 (Lumbricidae, Oligochaeta) - Narcis Mešič (Acta Biologica Slovenica, 1990)
The paper describes a new subgenus Alfolobophoridella subg.n. and three new species, namely: Allolobophora (Serbiona) mayeri sp.n., A. (S.) matjasici sp.n. and A. (S.) carnelullii sp.n. An attempt is made to solve some taxonomic problems involved in the genus Allolobophora sensu Mrsic and Sapkarev 1988.